Treating gambling disorder with as needed administration of intranasal naloxone: A pilot study to evaluate acceptability, feasibility and outcomes - Sari Castrén; Niklas Mäkelä; Janne Haikola; Anne H Salonen; Roger Crystal; Mika Scheinin; Hannu Alho (BMJ Publishing Group, 2022)
Background and aim There is growing interest in the use of medication-assisted treatments for gambling disorder (GD). Opioid receptor antagonists are hypothesised to blunt the craving associated with gambling. This study was designed to assess the feasibility of using an intranasal naloxone spray to treat GD.
Design An 8-week, open-label, uncontrolled pilot study.
Setting A single study site in the capital region of Finland.
Subjects Twenty problem gamblers (nine men) were randomised into two groups. Group A (n=10) took one dose into one nostril (2 mg naloxone), as needed, with a maximum of 4 doses/day (max. 8 mg/day). Group B (n=10) took one dose into each nostril (4 mg naloxone) as needed, with a maximum of 4 doses/day (max. 16 mg/day).
Intervention Naloxone hydrochloride nasal spray.
Measures Acceptability and feasibility of the intervention were assessed. Use of study medication, adverse events, gambling frequency and gambling expenditure were recorded in a mobile diary. Problem gambling: South Oaks Gambling Screen (SOGS), depressive symptoms: Beck Depression Inventory (BDI) and alcohol use: Alcohol Use Disorders Identification Test were recorded.
Results Study completion rate was 90%. Acceptability and feasibility scores were high. Group B used intranasal naloxone more frequently than group A, and consequently used more naloxone. No serious adverse events were reported. The postintervention SOGS scores were lower (median=4 (IQR=3.75) versus preintervention scores (median=12 (IQR=4.75)). Depressive symptoms were reduced during the trial (preintervention BDI median=9, IQR=9 vs postintervention BDI median=6, IQR=6).
Conclusions The acceptability and feasibility of using intranasal naloxone were high, and no serious adverse events were reported. Preliminary results suggest mixed results in terms of gambling behaviour (ie, reduced frequency but not expenditure) and decreased depressive symptoms.